Metodologías experimentales para optimización de diversas propiedades en la inyección de surfactantes mediante el uso de nanotecnología (2021)
The present work seeks to carry out a detailed and updated compilation of all the scientific advances in the area of ​​improved oil recovery through the combination of the conventional technique of injection of surfactants improved from the implementation of nanotechnology, taking into account the capacity that various materials on this scale have been shown to enhance the mechanisms of action of surfactant molecules, namely the interfacial tension in the water-oil system, the change in wettability of the storage rock, the decrease in the adsorption of surfactant in the throats porales of the reservoir and, consequently, a significant increase in capillary number